Pengembangan Media Pembelajaran Berbasis Aplikasi Sway dalam Pembelajaran Pendidikan Pancasila Pada Kurikulum Merdeka di Kelas II Sekolah Dasar - Aladzanna, Edyva; Waldi, Atri; Reinita; Erita, Yeni (Journal of Practice Learning and Educational Development, 2025)
Development of Sway Application-Based Media in Pancasila Education Learning in the Independent Curriculum in Grade II of Elementary School. Thesis. Elementary School Teacher Education. Faculty of Education. State University of Padang. Education plays a very important role in life. With education, one can learn various sciences and technologies. Based on the observations and interviews conducted by the researcher at SD Negeri Percobaan Padang, several pieces of information and problems were obtained. These include the fact that the school has provided teachers with LCD projectors and laptops to support the learning process, but these facilities are not yet fully utilized as learning media. Next, classroom teachers still frequently use the lecture method to deliver learning materials. This research falls into the R&D category, or Research and Development. The ADDIE model is the model used in this research and development. The five stages of developing the ADDIE model are: Analysis, Design, Development, Implementation, and Evaluation. Based on the media validation that has been carried out, the results of the validation by content experts were obtained with a percentage of 98% and categorized as Very Valid. Based on the media validation that has been carried out, the results of the validation by content experts were obtained with a percentage of 98% and categorized as Very Valid. Based on the language validation that has been carried out, the results of the validation by language experts were obtained with a percentage of 81% and categorized as Valid. The results of content validation were 95% with a very valid category, the results of media validation were 98% with a very valid category, and the results of language validation were 81% with a valid category. This provides an indication that the developed learning media is valid. Meanwhile, the results of the students' responses showed a practicality percentage of 96.8% with a "very practical" category. This indicates that the developed learning media can assist the learning process in the classroom.